2015
DOI: 10.5114/fn.2015.54424
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-210 regulates cell proliferation and apoptosis by targeting regulator of differentiation 1 in glioblastoma cells

Abstract: A b s t r a c t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 26 publications
2
35
0
3
Order By: Relevance
“…7 Like other malignant tumours, glioblastoma also exhibits abnormal cell proliferation and metastasis, which were caused by abnormal expression of a variety of genes. [8][9][10][11] C-type lectin domain family 5 member A (CLEC5A), also known as C-type lectin superfamily member 5 (CLECSF5) and myeloid DAP12associating lectin 1 (MDL1), is a C-type lectin encoded by CLEC5A gene. This gene encodes a member of C-type lectin/C-type lectinlike domain (CTL/CTLD) superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…7 Like other malignant tumours, glioblastoma also exhibits abnormal cell proliferation and metastasis, which were caused by abnormal expression of a variety of genes. [8][9][10][11] C-type lectin domain family 5 member A (CLEC5A), also known as C-type lectin superfamily member 5 (CLECSF5) and myeloid DAP12associating lectin 1 (MDL1), is a C-type lectin encoded by CLEC5A gene. This gene encodes a member of C-type lectin/C-type lectinlike domain (CTL/CTLD) superfamily.…”
Section: Introductionmentioning
confidence: 99%
“…One important miRNA is miR‐210, which is directly promoted by HIF1α and plays a key role in the hypoxic response. It has been reported to regulate various critical biological processes under hypoxia, such as cell cycle (He et al, ; Zuo et al, ), differentiation (Liu et al, ), apoptosis (Gou et al, ; Zhang et al, ), and mitochondrial metabolism (Chan et al, ; Chen et al, ; White et al, ), in many kinds of tumors. Moreover, clinical studies found that miR‐210 expression was significantly increased in OS tissues (Lulla et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to be involved in cell survival, differentiation, angiogenesis, metabolism and cell cycle control (15,44). In addition, elevated miR-210 levels increase the proliferation and decrease apoptosis of GBM cells by targeting polypyrimidine tract binding protein 3 (45). miR-210 extracted from the peripheral blood is a promising and minimally invasive biomarker that can be employed to diagnose and predict the outcome of glioma (27).…”
Section: Discussionmentioning
confidence: 99%